Multiple admissions to the coronary care unit due to falsely elevated cardiac troponin. Issue 2 (3rd April 2018) - Ayan, Mohamed; Gheith, Zaid; Ananthula, Aneesha; Salih, Mohsin; Vallurupalli, Srikanth; Mehta, Jawahar L.
ABSTRACT: The measurement of cardiac troponin, released from injured cardiomyocytes, is of paramount importance in the diagnosis of acute myocardial infarction. Elevated troponin can be encountered, however, in patients with cardiomyopathy, significant cardiac arrhythmias, vasculitis, right-sided heart strain, critical systemic illnesses, stroke, drug toxicity (such as Adriamycin), poisons (such as snake venoms), renal failure, seizure, and rhabdomyolysis. If the clinical picture is not consistent with any of these causes, a false-positive result should be considered. We herein describe a 94-year-old man with a prior history of coronary artery disease who presented with altered mental status and was found to have a persistently high troponin level resulting in three admissions to the coronary care unit for various noncardiac complaints. Because of discordance between clinical and laboratory data, immunological interference due to heterophile antibodies in the locally used assay (AccuTnI+3, Beckman Coulter) was suspected. The same serum sample tested on a different assay (Elecsys Troponin I Assay, Roche) resulted in an undetectable cardiac troponin I level, thus confirming the diagnosis.